The Urban Addition - Al-Hinkawi, Wahda Shuker; Zedan, Shereen Kamil (Iraqi Journal of Architecture and Planning, 2018)
The research Explore one of the important topics that emerged from the contemporary urban development policies, by adding new urban entities within the city fabric, which represented by the urban addition, which appeared at different levels, evolved gradually with different contemporary urban orientations, which began to call in at the beginning of the twentieth century to go back to the inner-city and their historic city centers and addition to it in order to develop. the concept of urban addition crystallized in many literatures that dealt with the relationship between the addition and origin, and the process of creating a new integrated, interactive, and communicative with the existing urban fabric, where the contemporary urban trends varied in its dealings with the Transition joint between the addition and the original by finding the transitions boundaries or dissolves within the fabric according to the value of that existing fabric (the origin), Whether it was historical, ecological, functional, natural, cultural or other values, Accordingly the Research problem defined as;" The Limits of the previous studies which is dealing with the mechanisms of the urban addition and the forces governing the relationship between the addition and origin". To deal with the research problem a theoretical framework has been built for the concept of urban Addition, in general, and the relationship between additive and origin, in particular. The research clarify the variation of additive types to the urban fabric, whether [conservative addition] within the historic fabric that contains a high historical value, or developmental Addition within.modern fabric characterized by the disintegrate and chaos, that you need to be organize through new urban extensions